Pengembangan LKPD berbasis Problem Based Learning (PBL) Konten Barisan dan Deret untuk Memfasilitasi Kemampuan Pemahaman Matematis Peserta Didik Fase E - Putri, Yolanda Amara; Armis, Armis; Yuanita, Putri (Papanda, 2025)
Mathematical comprehension ability is one of the most important aspects in learning mathematics, but the facts show that students' mathematical comprehension ability is still low, especially in the content of Sequences and Series. One effort to facilitate this problem is by using Student Worksheets based on Problem Based Learning. The purpose of this study is to develop valid and practical Student Worksheets. This development research refers to the 4D development model which includes define, design, develop, and disseminate. The instruments used are validation questionnaires and practicality questionnaires. The results of the validation questionnaire data analysis obtained that the Student Worksheets were categorized as very valid with an average percentage of 95.07%. The results of the practicality questionnaire data analysis obtained that the Student Worksheets were categorized as very practical with an average percentage of 89.38%. Thus, the Student Worksheets in this study have met the requirements for validity and practicality so that they can be used in learning activities. The implication of this study is to make it easier for students to build knowledge independently in mathematics learning so that mathematical comprehension abilities can be facilitated.